2012
DOI: 10.1051/limn/2012029
|View full text |Cite
|
Sign up to set email alerts
|

Responses in population growth and reproduction of the freshwater rotiferBrachionus calyciflorusto microcystin-LR at different temperatures

Abstract: -Microcystis blooms occur worldwide in eutrophic lakes. Microcystins (MCs) including microcystin-LR (MC-LR) released by Microcystis have adverse effects on aquatic organisms such as rotifers. To detect population growth and reproductive responses, the rotifer Brachionus calyciflorus was exposed to MC-LR at eight concentrations ranging from 0 to 200 mg.L x1 under different temperature (20, 25 and 30 xC), and population growth rate (r), ovigerous females/non-ovigerous females (OF/NOF) ratio, mictic females/amict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Rotaria rotatoria is an asexual freshwater bdelloid rotifer, which is the largest Metazoan group that reproduces using only parthenogenesis (Ricci & Melone 2000;Mark Welch & Meselson, 2000, Fontaneto et al 2008Birky 2011). A large number of investigations dealing with ecological and evolutionary responses of monogont rotifers to temperature have recently been conducted because of their highly susceptibility to physical and chemical changes in their environment due to their small size and peculiar parthenogenetic reproduction (Miracle & Serra 1989;Snell et al 1991;Nogrady et al 1993;Xiang et al 2010;Huang et al 2012;Pan et al 2014). However, few studies are available on the life history characteristics and population dynamics of bdelloid rotifers (see Ricci 1983Ricci , 1991Lebedeva & Gerasimova 1987;Ricci & Caprioli 1998;Santo et al 2001;Ricci & Covino 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Rotaria rotatoria is an asexual freshwater bdelloid rotifer, which is the largest Metazoan group that reproduces using only parthenogenesis (Ricci & Melone 2000;Mark Welch & Meselson, 2000, Fontaneto et al 2008Birky 2011). A large number of investigations dealing with ecological and evolutionary responses of monogont rotifers to temperature have recently been conducted because of their highly susceptibility to physical and chemical changes in their environment due to their small size and peculiar parthenogenetic reproduction (Miracle & Serra 1989;Snell et al 1991;Nogrady et al 1993;Xiang et al 2010;Huang et al 2012;Pan et al 2014). However, few studies are available on the life history characteristics and population dynamics of bdelloid rotifers (see Ricci 1983Ricci , 1991Lebedeva & Gerasimova 1987;Ricci & Caprioli 1998;Santo et al 2001;Ricci & Covino 2005).…”
Section: Introductionmentioning
confidence: 99%
“…higher temperatures (30°C) stimulate their population growth (81). Usually when two or more rotifer species compete for limited resources, one or more of them may be adversely affected by the presence of other (64) so the bad food quality is not the only limited factors for rotifers to taken into account.…”
Section: Rotifersmentioning
confidence: 99%
“…More, the toxin-producing Anabaena flos-aquae has been shown to decrease lifespan, fecundity, and population growth rate of the rotifers Brachionus calycijlorus and Synchaeta pectinata (33). Usually, MCs are released into water after demise of cells and dissolved MCs during the collapse of heavy blooms can come in contact with a wide range of aquatic organisms including rotifers and have adverse effects on them by increasing mortality (81). Notably is that when different species coexist in the ecosystem react different to the toxins (64).…”
Section: Rotifersmentioning
confidence: 99%
“…Ever since the early observations of Francis (1878) in Australia, several studies have confirmed the adverse effects of cyanotoxins on invertebrates and vertebrates (Whitton and Potts 2002). These studies were originally conducted using extracts from pure cultures of cyanobacteria (DeMott et al 1991; Ghadouani et al 2004; Huang et al 2012). In nature, however, several taxa of cyanobacteria may coexist, resulting in synergistic or antagonistic effects.…”
Section: Introductionmentioning
confidence: 99%